Silicon-based composite material, preparation method thereof and negative plate

By loading silicon nanoparticle particles with a gradient oxygen-rich layer in the porous substrate, the problem of volume expansion of silicon-based composite materials during lithium embedding/delithation is solved, and the cycle stability and conductivity of the battery are improved.

CN119725409APending Publication Date: 2025-03-28LANXI ZHIDE ADVANCED MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311255463.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Silicon-based composite materials will cause huge volume expansion/contraction during the lithium embedding/deliquefaction process, resulting in damage to the electrode structure, attenuation of battery capacity, and reduced circulation efficiency.

Method used

A plurality of silicon particles with silicon nanoparticles as the core and oxygen-rich layer as the shell are loaded in the porous substrate channel, and the oxygen content in the oxygen-rich layer varies in a gradient direction from the center of the silicon nanoparticles to the surface.

Benefits of technology

The conductivity of silicon-based composite materials is improved, and the volume expansion of silicon during lithium embedding is alleviated through an oxygen-enriched layer with a gradient of oxygen content changes, thereby reducing the electrode expansion rate, and thus improving the cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725409A_ABST
    Figure CN119725409A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-based composite material, a preparation method thereof and a negative plate. The silicon-based composite material comprises silicon-based composite material particles, the silicon-based composite material particles comprise a porous substrate and silicon particles loaded in pores of the porous substrate, the silicon particles comprise at least one silicon nanoparticle and an oxygen-enriched layer at least partially coating the silicon nanoparticle, the oxygen-enriched layer is made of SiOx, x is more than 0 and less than or equal to 2, and x is more than 0 and less than or equal to 2. And the oxygen content in the oxygen-rich layer is in gradient change along the direction from the center to the surface of the silicon nanoparticle. According to the silicon-based composite material provided by the invention, the plurality of silicon particles taking the silicon nanoparticles as the core and the oxygen-enriched layer as the shell are loaded on the porous substrate, and the oxygen content in the oxygen-enriched layer is in gradient change, so that the conductivity of the silicon-based composite material is improved; moreover, the volume expansion of silicon in the lithium intercalation process can be relieved by utilizing the oxygen-enriched layer with the gradient change of the oxygen content, the expansion rate of the electrode is reduced, and the cycle performance of the battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a silicon-based composite material, a preparation method thereof, and a negative electrode sheet. Background Art

[0002] Silicon is an alloyed lithium-intercalation material with a theoretical lithium-intercalation capacity of up to 4200mAh / g. It is abundant in resources, safe and non-toxic, and is currently one of the most promising negative electrode materials for lithium-ion batteries to replace carbon materials. There are two problems with silicon as a negative electrode material for lithium-ion batteries. First, silicon has poor conductivity, which can be solved by various methods such as carbon carriers, carbon blending, and carbon coating. Second, silicon will produce huge volume expansion / contraction during the lithium-intercalation / de-lithiation process, which will lead to damage to the electrode structure, battery capacity decay, and reduced cycle efficiency.

[0003] In recent years, by optimizing silicon particle size, distribution and adjusting the structure of negative electrode materials, the volume expansion of silicon-based composite materials such as silicon-oxygen negative electrode materials and silicon-carbon negative electrode materials has been greatly reduced. However, this improvement is far from enough for practical applications. How to reduce the volume expansion of silicon-based composite materials during charging and discharging and significantly increase the cycle life is an important issue that needs to be solved urgently.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The main purpose of the present invention is to provide a silicon-based composite material and a preparation method thereof, a negative electrode sheet, a battery and an electrical terminal, so as to solve the problem in the prior art that the silicon-based composite material will produce huge volume expansion / contraction during the lithium insertion / delithiation process, resulting in electrode structure damage, battery capacity attenuation and reduced cycle life.

[0006] In order to achieve the above object, according to one aspect of the present invention, a silicon-based composite material is provided, the silicon-based composite material comprises silicon-based composite material particles, the silicon-based composite material particles comprise a porous substrate and silicon particles supported on the porous substrate, the silicon particles comprise at least one silicon nanoparticle and an oxygen-rich layer at least partially coated on the silicon nanoparticle, the material of the oxygen-rich layer is SiO x , 0<x≤2, and the oxygen content in the oxygen-rich layer changes gradiently along the direction from the center to the surface of the silicon nanoparticle.

[0007] According to another aspect of the present invention, a method for preparing a silicon-based composite material is provided, and the preparation method comprises the following steps: step S1, providing a porous substrate; step S2, contacting the porous substrate with a silicon-containing precursor and an oxygen-containing precursor, performing silicon deposition and oxygen deposition, and obtaining a silicon-based composite material; optional step S3, performing deep oxidation treatment on the composite material obtained in step S2; optional step S4, coating the composite material obtained in step S2.

[0008] According to another aspect of the present invention, a negative electrode is provided. The negative electrode comprises a negative electrode active material. The negative electrode active material is any one of the above silicon-based composite materials or a silicon-based composite material obtained by any one of the above preparation methods.

[0009] By applying the technical solution of the present invention, the silicon-based composite material provided by the present application loads a plurality of silicon particles with silicon nanoparticles as the core and an oxygen-rich layer as the shell in the pores of a porous substrate, and the oxygen content in the oxygen-rich layer varies in a gradient, which is not only beneficial to improving the conductivity of the silicon-based composite material, but also can utilize the oxygen-rich layer with a gradient variation in oxygen content to alleviate the volume expansion of silicon during the lithium insertion process, reduce the electrode expansion rate, and thereby improve the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0011] Figure 1 A mapping diagram of the silicon-based composite material provided according to Example 1 of the present invention is shown. DETAILED DESCRIPTION

[0012] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0013] As mentioned in the background technology of this application, silicon is one of the most promising negative electrode materials for lithium-ion batteries to replace carbon materials. However, the huge volume expansion / contraction of silicon during the lithium insertion / delithiation process can lead to a series of problems. In order to solve this problem, this application provides a silicon-based composite material, a preparation method thereof, and a negative electrode sheet.

[0014] In a first typical embodiment of the present application, a silicon-based composite material is provided, the silicon-based composite material comprises silicon-based composite material particles, the silicon-based composite material particles comprise a porous substrate and silicon particles loaded in the pores of the porous substrate, the silicon particles comprise at least one silicon nanoparticle and an oxygen-rich layer at least partially coated on the silicon nanoparticle, the material of the oxygen-rich layer is SiO x , 0<x≤2, and the oxygen content in the oxygen-rich layer changes gradually from the center to the surface of the silicon nanoparticle. x Here, x is 0.01, 0.05, 0.1, 0.2, 0.5, 0.8, 1.0, 1.2, 1.5, 1.8, 2.0 or a range consisting of any two values.

[0015] By applying the technical solution of the present application, the silicon-based composite material provided by the present application loads a plurality of silicon particles with silicon nanoparticles as the core and an oxygen-rich layer as the shell in the pores of a porous substrate, and the oxygen content in the oxygen-rich layer varies in a gradient. This is not only beneficial to improving the conductivity of the silicon-based composite material, but also can utilize the oxygen-rich layer with a gradient variation in oxygen content to alleviate the volume expansion of silicon during the lithium insertion process, reduce the electrode expansion rate, and thereby improve the cycle performance of the battery.

[0016] In some embodiments of the present application, the oxygen-rich layer (also referred to as SiO x The porous substrate and the silicon nanoparticles may be formed by a small amount of oxygen-containing functional groups remaining on the surface of the porous substrate after incomplete carbonization and / or by an oxide layer formed on the surface of the porous substrate after oxidation of the porous substrate. When silicon is deposited on the porous substrate, SiO2 is formed between the porous substrate and the silicon nanoparticles. x interface; secondly, SiO2 on the surface of silicon nanoparticles and / or between silicon nanoparticles x The layer is obtained by treating silicon nanoparticles with oxygen, SiO x The layer at least partially covers the surface of the silicon nanoparticles. x It can restrain the volume expansion of silicon nanoparticles and improve the cycle stability of silicon particles.

[0017] In addition, the content of oxygen atoms in the silicon-based composite material has the characteristic of changing gradually from the center to the surface of the silicon-based composite material. This change mainly comes from the SiO x The distribution of SiO in silicon particles x The thickness of the layer and the size of x (x determines the gradient change of the oxygen atom content in the silicon-based composite material). SiO x The thickness of the layer and the size of x are related to the oxygen concentration, oxidizability, treatment temperature, and treatment time of the oxygen-containing precursor and / or oxygen-containing substance during the oxygen-containing treatment process, and affect the content of oxygen atoms in the composite material, while the timing and number of oxygen-containing treatments affect the change in the oxygen atom content of the silicon-based composite material from the center along the radial direction to the surface. In some embodiments, the change in the oxygen atom content of the silicon-based composite material from the center along the radial direction to the surface can present a step-by-step increase, a step-by-step decrease, or a periodic gradient change, etc.

[0018] In order to further improve the lithium insertion capacity and cycle stability of the material, the material of the silicon nanoparticles is preferably simple silicon, and the particle size of the silicon nanoparticles is 0.5 to 10 nm, especially when the particle size of the silicon nanoparticles is 0.5 to 2 nm, which is more conducive to improving the volume stability of the negative electrode material during lithium insertion and delithiation. In the present application, the particle size of the silicon nanoparticles is 0.5 nm, 0.8 nm, 1 nm, 2 nm, 5 nm, 8 nm, 10 nm, or a range of any two values.

[0019] In order to further alleviate the volume effect of silicon during lithium insertion / extraction, the thickness of the oxygen-rich layer is preferably 0.5-5 nm, preferably 0.5-1 nm, and the thickness of the oxygen-rich layer is not greater than the particle size of the silicon nanoparticles. x The thinner interface is conducive to the loading of silicon nanoparticles on the porous substrate and improves the strength of the composite material; the oxygen-rich layer (SiO x The layer can restrain the lithium expansion of silicon, but if it is too thick, it will not be able to play an effective buffering role.

[0020] In some embodiments, the SiO x The x in the figure increases gradually from the center to the surface of the silicon nanoparticle. For example, the silicon oxides coated on the surface of the silicon nanoparticle are Si, SiO, and SiO2 in sequence. The larger the x value, the corresponding SiO x The lower the volume expansion during lithium insertion, the more it can buffer and restrain the internal volume expansion. x The cycle stability of silicon particles can be further improved.

[0021] In some embodiments, the content of oxygen atoms in the oxygen-rich layer increases gradually from the center to the surface of the silicon-based composite material. In order to further improve the electrochemical performance of the negative electrode material, the outer surface of the oxygen-rich layer has a step-increase in oxygen content compared to the inner portion thereof, and the thickness of the oxygen-rich layer is 0.5 to 5 nm.

[0022] In the present application, the thickness of the oxygen-rich layer is, for example, 0.5 nm, 1 nm, 2 nm, 5 nm, or a range of any two values. The oxygen-rich layer can restrain the volume expansion of the negative electrode material from the inside to the outside, reduce the expansion rate of the composite electrode, and improve the cycle performance of the battery. However, if the oxygen-rich layer is too thick, the oxygen content in the negative electrode material will increase, resulting in a decrease in the first efficiency.

[0023] In order to further improve the capacity of lithium insertion, in some embodiments, it is preferred that the mass content of silicon in the above silicon-based composite material is 5-95% (such as 5%, 8%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, etc.). Silicon is the key to improving the capacity of silicon-based composite materials. When the silicon content is low, the capacity of silicon-based composite materials is greatly limited and cannot meet the needs of practical applications; when the silicon content is high, the porous matrix needs to have a higher specific surface area, and the uniformity of the siliconization process is also very high, which can easily cause a large amount of silicon-rich surface, resulting in poor battery kinetic performance, so it is necessary to control the appropriate silicon content. In some embodiments, the mass content of silicon is 30-70%, and the composite material has better comprehensive performance.

[0024] In order to further improve the cycle efficiency of the battery, in some embodiments, it is preferred that the mass content of oxygen in the above-mentioned silicon-based composite material is 0.5-10% (such as 0.5%, 0.8%, 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 10%, etc.), especially when the mass content of oxygen is 1-5%, the silicon-based composite material has a higher battery cycle efficiency.

[0025] If the oxygen content is too high, the excess oxygen will react irreversibly with lithium during the lithium insertion process, resulting in the loss of reversible lithium capacity and reduced battery initial efficiency and cycle efficiency. If the oxygen content is too low, sufficient SiO x To alleviate the volume effect of silicon, resulting in poor battery cycle stability.

[0026] In order to further improve the stability of the silicon-based composite material during lithium insertion or removal, the specific surface area of ​​the silicon-based composite material is preferably 0.5 to 50 m 2 / g, especially when the specific surface area of ​​the silicon-based composite material is 0.5 to 10 m 2 / g, because the porous matrix has a higher specific surface area, greater activity, and lower initial efficiency of the battery; the composite material needs to reach an extremely low specific surface area after siliconization to reduce the side reactions on the surface of the material and improve the cycle efficiency. Therefore, the lower the specific surface area of ​​the silicon-based composite material, the better. However, when the specific surface area is less than 1.0m 2 / g, it is usually very difficult to further reduce the specific surface area, so the minimum specific surface area of ​​the composite material in this application is 0.5m 2 / g.

[0027] Compacted specific surface area (the silicon-based composite material is 4000kgf / cm 2 The specific surface area of ​​the material after compaction under pressure reflects the structural strength of the material. xWhen silicon nanoparticles are separated and bound, the structural strength of the material is high, which will improve the mechanical stability in battery applications. In some embodiments, the compacted specific surface area of ​​the silicon-based composite material is 1 to 20 times, preferably 1 to 10 times, and more preferably 1 to 5 times the specific surface area of ​​the silicon-based composite material.

[0028] In some embodiments, the compacted density of the silicon-based composite material is 0.8 to 1.5 g / cm 3 , such as 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.5g / cm 3 Or a range of any two values.

[0029] In some embodiments, the resistivity of the silicon-based composite material is 1 to 1000Ω·cm (such as 1Ω·cm, 10Ω·cm, 50Ω·cm, 100Ω·cm, 300Ω·cm, 500Ω·cm, 800Ω·cm, 1000Ω·cm or any value therebetween) so that the silicon-based composite material has better conductivity.

[0030] Since SiO x In the presence of, the silicon-based composite material exhibits a certain acidity. In some embodiments, the pH value of the silicon-based composite material is 3.0 to 7.5 (such as 3.0, 3.5, 5, 5.5, 6, 6.5, 7.0, 7.5, etc.).

[0031] The shape of the silicon-based composite material particles is not particularly limited, and includes but is not limited to one or more of sphere, ellipsoid, quasi-spherical, and irregular polygon.

[0032] In some embodiments, the median particle size d of the silicon-based composite material is V,50 5~20μm, diameter distance (d V,90 -d V,10 ) / d V,50 is 0.8 to 2.0; preferably, the median particle size d of the silicon-based composite material V,50 6~12μm, diameter distance (d V,90 -d V,10 ) / d V,50 It is 0.8~1.2.

[0033] The specific type of the above-mentioned porous substrate is not limited, including but not limited to porous carbon, porous metal, porous metal oxide, porous metal-organic framework material, porous organic-inorganic hybrid material, any one or more of the composite porous substrate formed by two or more. Preferably, the porous substrate is selected from porous carbon, more preferably, the porous carbon can be selected from one or more of soft carbon, hard carbon, carbon black, graphite, graphene, carbon nanotubes, carbon fiber, mesophase carbon microspheres; it can also be made by pyrolysis and / or activation of the carbon precursor to obtain porous carbon. The carbon precursor includes a combination of one or more of polymer precursors, biomass precursors, and fossil carbon sources. For example, sugars such as glucose, sucrose, maltose, lactose, cyclodextrin, starch, glycogen, cellulose, hemicellulose, lignin, etc.; composite resins such as epoxy resin, thermoplastic phenolic resin, thermosetting phenolic resin, polyoxymethylene resin, urea-formaldehyde resin, furfural resin, furfural ketone resin, acrylic resin, coconut shell, rice husk, wood; coal, asphalt, petroleum coke, etc. Fossil carbon sources include coal, asphalt, petroleum coke, etc.

[0034] In some specific embodiments of the present application, porous carbon is prepared in the following manner: sucrose is heated to 800°C at 2°C / min in a N2 atmosphere and maintained for 2 hours, heated to 900°C in a mixture of CO2 and N2 (the volume fraction of CO2 is 20%) and maintained for 2 hours, and the sintered material is cooled and crushed and graded to obtain porous carbon with a particle size of 20 μm.

[0035] In some embodiments, the specific surface area of ​​the porous substrate is 200 to 3000 m 2 / g, total pore volume is 0.2~3.0cm 3 / g. Further preferably, the specific surface area of ​​the porous substrate is 600 to 2000 m 2 / g, total pore volume is 0.4~1.5cm 3 Typically, but not limiting, the specific surface area of ​​the porous substrate is 600 m 2 / g、800m 2 / g、1000m 2 / g、1200m 2 / g、1500m 2 / g、1800m 2 / g, 2000m 2 / g、2500m 2 / g、3000m 2 / g or a range of two values, such as a total pore volume of 0.2cm 3 / g, 0.5cm 3 / g, 0.8cm 3 / g, 1.0cm 3 / g, 1.5cm 3 / g, 2.0cm3 / g, 2.5cm 3 / g, 3.0cm 3 / g or a range of any two values.

[0036] In other embodiments, the silicon-based composite material further includes a coating layer, which is coated on the surface of the porous substrate (silicon-based composite material particles) loaded with silicon particles to further improve the stability and conductivity of the silicon-based composite material.

[0037] The specific material of the coating layer is not limited, including but not limited to a composite coating layer formed by one or more of solid electrolytes, conductive polymers, carbonaceous materials, metal elements, alloys, and metal oxides. The material of the coating layer can be lithium hydroxide, lithium carbonate, lithium fluoride, lithium phosphate, lithium metaphosphate, aluminum dihydrogen phosphate, lithium metaaluminate, lithium aluminum phosphate, aluminum phosphate, aluminum metaphosphate, aluminum oxide, monohydrated aluminum oxide, trihydrated aluminum oxide, aluminum hydroxide, aluminum sol, aluminum isopropoxide, magnesium oxide, magnesium hydroxide, zinc oxide, zinc hydroxide, titanium oxide, zirconium oxide, LiPON (lithium phosphorus oxygen nitrogen), LLZO (lithium lanthanum zirconium oxygen), LATP (lithium aluminum titanium phosphate), LLTO (lithium lanthanum titanium oxide), lithium germanium phosphorus sulfur compounds One or more; can also be polyethylene oxide, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile and other polymers and lithium complexes thereof One or more; at the same time, it can also be LISICON type solid electrolyte, NASICION type solid electrolyte, perovskite type solid electrolyte, garnet type solid electrolyte, sulfide solid electrolyte One or more.

[0038] In order to further improve the ion transmission efficiency, the thickness of the coating layer is preferably 2 to 200 nm, more preferably 2 to 50 nm, and more preferably 2 to 10 nm.

[0039] In a second typical embodiment of the present application, a method for preparing a silicon-based composite material is also provided, and the preparation method comprises the following steps: step S1, providing a porous substrate; step S2, contacting the porous substrate with a silicon-containing precursor and an oxygen-containing precursor, performing silicon deposition and oxygen deposition, and obtaining a silicon-based composite material; wherein, in step S2, silicon deposition and oxygen deposition are performed simultaneously, or silicon deposition is performed first and then oxygen deposition is performed, or the two are performed alternately in a cycle.

[0040] Optionally, the preparation method further comprises a step S3 arranged after the step S2, which is a deep oxidation treatment to further improve the stability of the silicon-based composite material.

[0041] Optionally, the preparation method further comprises step S4, which is arranged after step S2, of coating treatment.

[0042] Both the coating treatment and the deep oxidation treatment can be carried out, and the order of the two treatments is not limited.

[0043] The preparation method of the silicon-based composite material provided in the present application has a simple process, is easy to operate, is conducive to large-scale production, and effectively reduces production costs.

[0044] In some embodiments of the present application, silicon deposition includes: placing a porous substrate in a silicon-containing precursor atmosphere so that silicon is deposited in the pores of the porous substrate to form silicon nanoparticles; wherein the silicon-containing precursor includes but is not limited to a mixture of any one or more of monosilane, disilane, trisilane, halosilanes, polysilanes, silole and its derivatives, and silane and its derivatives.

[0045] In some embodiments of the present application, oxygen deposition includes: placing the material to be vapor deposited in a chemical vapor deposition furnace, introducing a gas containing an oxygen-containing precursor, and obtaining a material treated with oxygen phase deposition; wherein the oxygen-containing precursor includes a mixture of any one or more of oxygen, carbon dioxide, water vapor, methanol, ethanol, n-propanol, isopropanol, butanol, acetone, and butanone.

[0046] In some specific embodiments, the atmosphere of the above-mentioned silicon-containing precursor and / or oxygen-containing precursor may include, in addition to the silicon-containing precursor and / or oxygen-containing precursor, an inert gas, and the inert gas is selected from one or more of N2, Ar, and He; in some preferred embodiments, in the atmosphere of the silicon-containing precursor and / or oxygen-containing precursor, the volume content of the silicon-containing precursor and / or oxygen-containing precursor is 1 to 50%.

[0047] In order to further improve the efficiency of silicon deposition and / or oxygen deposition, it is preferred that the temperature of silicon deposition and / or oxygen-containing deposition is 200-1000°C (such as 200°C, 300°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 800°C, 900°C, 1000°C, etc.), and the time is 0.5-100h (0.5h, 0.8h, 1.0h, 2.0h, 5.0h, 10h, 15h, 20h, 40h, 60h, 80h, 100h, etc.).

[0048] In some embodiments, the above-mentioned deep oxidation treatment includes chemical oxidation, solid-liquid separation and sintering performed in sequence, wherein the chemical oxidation includes: placing the composite material obtained by silicon deposition and oxygen deposition in step S2 in a solution containing an oxidant for chemical oxidation treatment; wherein the oxidant includes but is not limited to at least one of HNO3, H2SO4, acetic acid, propionic acid, butanol, butyric acid, succinic acid, malic acid, citric acid, and potassium permanganate.

[0049] In some specific embodiments, the chemical oxidation comprises: dispersing the composite material obtained by silicon deposition and oxygen deposition in a solution containing an oxidant and contacting the solution at 0 to 50° C. for 0.5 to 12 hours for chemical oxidation treatment.

[0050] In some specific embodiments of the present application, the preparation method of the silicon-based composite material is carried out according to the following steps:

[0051] Providing a porous substrate; placing the porous substrate in an atmosphere containing a silicon precursor to perform silicon deposition to form silicon nanoparticles deposited in the pores of the porous substrate, thereby obtaining a porous substrate loaded with silicon nanoparticles; placing the porous substrate loaded with silicon nanoparticles in an atmosphere containing an oxygen precursor to perform oxygen chemical vapor deposition to form an oxygen-rich layer on the surface of the silicon nanoparticles to generate silicon particles, and optionally repeating the above steps 1 to 50 times in sequence; and finally dispersing the material after chemical vapor deposition in a potassium permanganate solution (0.2 to 2M) to perform chemical oxidation treatment to obtain a silicon-based composite material.

[0052] In other embodiments, the method for preparing the silicon-based composite material also includes coating the surface of the silicon-based composite material particles to form a coating layer to obtain a silicon-based composite material having a coating layer; wherein the material of the coating layer has the same meaning as in the first aspect mentioned above and will not be repeated here.

[0053] In a third typical embodiment of the present application, a negative electrode sheet is also provided, which contains a negative electrode active material. The negative electrode active material is any silicon-based composite material provided in the above-mentioned first typical embodiment or a silicon-based composite material obtained according to any preparation method provided in the second typical embodiment.

[0054] The negative electrode sheet provided in the present application adopts the above silicon-based composite material as the negative electrode active material, which is more conducive to improving the volume expansion of the negative electrode sheet, thereby improving the cycle stability of the battery and extending its service life.

[0055] In a fourth typical embodiment of the present application, a battery is further provided. The battery includes the negative electrode sheet provided in the third typical embodiment, thereby being able to more effectively improve the cycle stability and extend the service life.

[0056] In the fifth typical embodiment of the present application, an electric device is also provided, the power supply of the electric device is the battery provided in the above-mentioned fourth typical embodiment, so that the power supply of the electric device is more stable, which is more conducive to improving the use stability of the electric device.

[0057] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.

[0058] Example 1

[0059] The present embodiment provides a silicon-based composite material, which includes a porous substrate and a plurality of silicon particles loaded in the pores of the porous substrate, wherein the silicon particles include at least one silicon nanoparticle and an oxygen-rich layer at least partially coated on the silicon nanoparticle, wherein the material of the oxygen-rich layer is SiOx (0<x≤2), and x increases gradually from the center to the surface of the silicon nanoparticles covered by the oxygen-rich layer; wherein the porous substrate is porous carbon with a specific surface area of ​​1540m 2 / g, with a total pore volume of 0.7 cm 3 / g, the particle size of the plurality of silicon nanoparticles is 0.5-2 nm, the thickness of the oxygen-rich layer is 0.5-2 nm, and in the silicon particles, the thickness of the oxygen-rich layer is not greater than the thickness of the silicon nanoparticles coated by the oxygen-rich layer.

[0060] The silicon-based composite material is prepared according to the following steps:

[0061] The porous carbon was placed in an atmosphere furnace, heated from room temperature to 600°C at 2°C / min in a N2 atmosphere, and maintained at 600°C for 2h in an atmosphere of a first mixed gas of SiH4 and N2 (the volume content of SiH4 is 20%) to perform silicon deposition; then the first mixed gas was changed to N2, cooled to 200°C, and then changed to a second mixed gas of 0.01% O2-N2 (the volume content of oxygen is 0.01%), and maintained at 200°C for 12min for oxygen-containing treatment; then the second mixed gas was changed to N2 and heated to 600°C, and silicon deposition-oxygen-containing chemical vapor deposition treatment was performed on the porous carbon for 15 cycles, and then naturally cooled under the protection of N2, and a silicon-based composite material was obtained after crushing and grading. The silicon content of the obtained silicon-based composite material is 48.9%, the oxygen content is 2.8%, and the d V,50 9μm, the diameter distance (d V,90 -d V,10 ) / d V,50 It is 0.98.

[0062] Figure 1 This is a mapping photo of the silicon-based composite material obtained in Example 1, with a scale of 40nm. The distribution of oxygen elements can be seen as a layered structure with a significantly increased concentration. This layered structure is located on the surface of the silicon-containing composite material particles and is an oxygen-rich layer of the silicon-based composite material particles in the sense of micron particles. Since the theoretical size of the silicon nanoparticles in this application is 5nm or even below 2nm, which is determined by the pore structure of the porous matrix and the siliconization process, it is difficult to detect the silicon nanoparticles and the oxygen-rich layer and oxygen distribution on their surface using conventional detection methods. The oxygen gradient distribution in the oxygen-rich layer on the surface of the silicon nanoparticles in this application is a material structural feature that is reasonably inferred based on the preparation method. Figure 1 The middle oxygen-rich layer is the manifestation of the oxygen gradient distribution at the microscopic level in the macroscopic structure of micron particles.

[0063] Example 2

[0064] This embodiment provides a silicon-based composite material, and the porous carbon used has a specific surface area of ​​305m 2 / g, pore volume is 0.25cm 3 / g.

[0065] The silicon-based composite material is prepared according to the following steps:

[0066] The porous carbon was placed in an atmosphere furnace, and the temperature was raised from room temperature to 600°C at a rate of 2°C / min in a N2 atmosphere. The temperature was maintained at 600°C for 2 hours in an atmosphere of a first mixed gas of SiH4 and N2 (the volume content of SiH4 is 20%) to carry out silicon deposition. Then, the introduction of SiH4 was stopped and only N2 was introduced. After cooling to 400°C, the temperature was changed to a second mixed gas of CO2 and N2 (the volume content of CO2 is 1%), and the temperature was maintained at 400°C for 0.2 hours in the atmosphere of the second mixed gas to carry out oxygen atom deposition. Silicon deposition and oxygen atom deposition were cycled on the porous carbon for 3 times in sequence, and the temperature was naturally lowered under the protection of N2; the temperature was raised to 600°C in a N2 atmosphere, and the temperature was changed to 10% C2H2-N2 and maintained for 2 hours. A silicon-based composite material was obtained after crushing and grading. The silicon content, oxygen content, and d V,50 9μm, the diameter distance (d V,90 -d V,10 ) / d V,50 It is 0.98.

[0067] Example 3

[0068] This embodiment provides a silicon-based composite material, and the porous carbon used has a specific surface area of ​​1592 m 2 / g, pore volume is 1.20cm 3 / g.

[0069] The silicon-based composite material is prepared according to the following steps: placing porous carbon in an atmosphere furnace, heating from room temperature to 600°C at a rate of 2°C / min in a N2 atmosphere, maintaining at 600°C for 2.5 hours in an atmosphere of a first mixed gas of SiH4 and N2 (the volume content of SiH4 is 20%), performing silicon deposition, and then stopping the introduction of SiH4 and introducing only N2. After cooling to 200°C, changing to a second mixed gas of O2 and N2 (the volume content of O2 is 0.01%), maintaining at 200°C for 0.1 hour in the atmosphere of the second mixed gas, and performing oxygen atom deposition. Silicon deposition and oxygen atom deposition are cycled 20 times on the porous carbon in sequence, and the temperature is naturally lowered under the protection of N2. The silicon-based composite material is obtained after crushing and grading. The silicon content of the obtained silicon-based composite material is 81.2%, the oxygen content is 5.2%, and the d V,50 9μm, the diameter distance (d V,90 -d V,10 ) / d V,50 It is 0.98.

[0070] Example 4

[0071] The difference between this embodiment and embodiment 1 is that, on the basis of embodiment 1, a deep oxidation treatment step is added:

[0072] The silicon-based composite material obtained in Example 1 was dispersed in a 0.5M KMnO4 water / ethanol (water and ethanol volume ratio 50:50) solution, ultrasonically dispersed for 2 hours, stirred at 50°C for 2 hours, filtered, and the obtained solid was dried and calcined (maintained at 400°C for 2 hours in a N2 atmosphere) to obtain a silicon-based composite material. The silicon content of the obtained silicon-based composite material was 47.2%, the oxygen content was 4.5%, and the d V,50 9μm, the diameter distance (d V,90 -d V,10 ) / d V,50 It is 0.98.

[0073] Example 5

[0074] The difference between this embodiment and embodiment 1 is that, on the basis of embodiment 1, a coating step is added:

[0075] The silicon-based composite material obtained in Example 1 was dispersed in the graphene dispersion, ultrasonically dispersed for 2 hours, stirred at 50°C for 2 hours, and spray-dried to obtain a silicon-based composite material. The silicon content of the obtained silicon-based composite material was 48.2%, the oxygen content was 3.2%, and the d V,50 9μm, the diameter distance (d V,90 -d V,10 ) / d V,50 It is 0.98.

[0076] Example 6

[0077] The difference between this embodiment and embodiment 1 is that, on the basis of embodiment 1, a deep oxidation treatment step and a coating step are added:

[0078] The silicon-based composite material obtained in Example 1 was dispersed in a 0.5M KMnO4 water / ethanol (water and ethanol volume ratio 50:50) solution, ultrasonically dispersed for 2 hours, stirred at 50°C for 2 hours, filtered, and the obtained solid was dried and calcined (maintained at 400°C for 2 hours in a N2 atmosphere) to obtain a silicon-based composite material I;

[0079] The silicon-based composite material I was dispersed in the graphene dispersion, ultrasonically dispersed for 2 hours, stirred at 50°C for 2 hours, and mist dried to obtain a silicon-based composite material. The silicon content of the obtained silicon-based composite material was 47.0%, the oxygen content was 4.8%, and the V,50 9μm, the diameter distance (d V,90 -d V,10 ) / d V,50 It is 0.98.

[0080] Comparative Example 1

[0081] This comparative example uses the same porous carbon material as the porous substrate as Example 1, and the subsequent vapor deposition process is as follows:

[0082] The porous carbon was placed in an atmosphere furnace, heated from room temperature to 600°C at 2°C / min in a N2 atmosphere, maintained at 600°C for 30 hours in an atmosphere of a first mixed gas of SiH4 and N2 (the volume content of SiH4 was 20%), and silicon was deposited. Then, the temperature was naturally lowered under the protection of N2, and a silicon-based composite material was obtained after crushing and classification. The silicon content of the obtained silicon-based composite material was 48.9%, the oxygen content was 2.8%, and the d V,50 9μm, the diameter distance (d V,90 -d V,10 ) / d V,50 It is 0.98.

[0083] Powder compaction density test:

[0084] The silicon-based composite materials provided in the above-mentioned embodiments and comparative examples were tested for particle compaction density by a compaction density instrument, and the compaction density test data was obtained by maintaining the pressure at 1 t for 10 seconds.

[0085] Powder resistivity test:

[0086] The silicon-based composite materials provided in the above examples and comparative examples were tested for powder resistivity at a pressure of 20 MPa using a ST2722-SZ four-probe powder resistivity tester produced by Suzhou Jingge Electronics Co., Ltd.

[0087] Powder pH Test:

[0088] The silicon-based composite materials provided in the above examples and comparative examples were mixed with deionized water in a mass ratio of 1:9, filtered, and the pH value of the filtrate was tested with a pH meter.

[0089] Electrode, half-cell preparation and electrochemical performance testing:

[0090] The silicon-based composite material provided in the above embodiments and comparative examples was used as the negative electrode active material, and the silicon-based composite material, the conductive agent carbon black and the binder polyacrylic acid were mixed in a mass ratio of 8:1:1, and an appropriate amount of deionized water was added to prepare a slurry, and the slurry was coated on a copper foil to prepare a negative electrode sheet. The negative electrode sheet was prepared using a conventional method to prepare a CR2032 button battery, and the battery was tested for electrical performance. The specific test method is:

[0091] (1) Half-cell assembly: CR2032 button cells were assembled in a glove box, with lithium metal sheets as counter electrodes, polypropylene microporous membranes as separators, and the electrolyte being LiPF6 dissolved in a mixture of ethyl carbonate (EC) and diethyl carbonate (DEC) (volume ratio EC:DEC = 1:1), where the LiPF6 concentration was 1 mol / L.

[0092] The battery is charged and discharged using the LAND battery testing system.

[0093] (2) Cyclic gram capacity and first efficiency test: After the CR2032 battery is left uncharged for 6 hours, it is discharged at 0.05C to 0.005V, and then discharged at 0.01C to 0.005V; after standing for 5 minutes, it is charged to 1.5V at 0.05C constant current; the first lithium removal gram capacity is the gram capacity (or mass specific capacity) of the electrode material, and the ratio of the first lithium removal capacity to the first lithium insertion capacity is the first coulombic efficiency of the battery.

[0094] Full battery preparation and electrochemical performance testing:

[0095] The silicon-based composite materials provided in the above embodiments and comparative examples were used as negative electrode active materials. The pole pieces containing the negative electrode active materials were prepared into soft-pack batteries by conventional methods and the electrical performance tests were performed. The soft-pack batteries were prepared in a dehumidification room with a dew point of -45°C. The battery was subjected to charge and discharge cycle tests using a LANBTS battery testing system. The specific test method was as follows:

[0096] (1) Preparation of positive electrode sheet: The positive electrode active material LiCoO2, the conductive agent SuperP, the binder PVDF and the solvent NMP were stirred and mixed in a mass ratio of 92:3:5:150, and then evenly coated on the positive electrode collector, and then dried at 80°C to obtain the positive electrode sheet.

[0097] (2) Preparation of negative electrode sheet: The negative electrode active material, conductive agent SuperP, binder polyacrylic acid and solvent deionized water were stirred and mixed in a mass ratio of 95:1:4:120, and then evenly coated on the negative electrode collector, and then dried at 100°C to obtain the negative electrode sheet.

[0098] (3) The positive electrode sheet and the negative electrode sheet are stacked in a square shape and separated by a polypropylene separator to form a battery core, which is then packaged into an aluminum-plastic bag. An electrolyte with a corresponding capacity is injected into the aluminum-plastic bag, and the bag is vacuum-sealed to obtain a soft-pack battery. The electrolyte is a mixture of LiPF6, EC and DEC, wherein the concentration of LiPF6 is 1 mol / L and the volume ratio of EC to DEC is 1:1.

[0099] (4) Formation and Capacity Separation: After the battery is filled and sealed, it begins to form and is placed in a constant temperature box at 25°C for 12 hours. It is then charged to 3.3V at 0.02C constant current and allowed to stand for 30 minutes. It is then charged to 3.8V at 0.025C constant current and allowed to stand for 10 minutes. It is then charged to 4.2V at 0.33C constant current. The formed battery is vacuumed and the air bag is cut. Then, the battery is divided into capacities. It is charged to 4.45V at 0.33C constant current and allowed to stand for 10 minutes. It is then discharged to 3V at 1C constant current and allowed to stand for 10 minutes. It is then discharged to 3V at 0.33C constant current and allowed to stand for 3 minutes. The battery is then divided into capacities.

[0100] (5) 25℃ cycle test: The battery was placed in a 25℃ constant temperature box, charged to 4.45V at 1C constant current, and then charged to 0.1C at 4.45V constant voltage; after standing for 10 minutes, discharged to 3.0V at 1C constant current, and stood for 10 minutes. The above charging and discharging steps were repeated until the discharge capacity was lower than 80% of the first cycle discharge capacity. The number of cycles obtained at this time is the cycle life of the soft-pack battery; the capacity retention rate after 100 cycles was recorded.

[0101] The electrochemical performance test results of the silicon-based composite materials prepared in each embodiment and comparative example are shown in Table 1 and Table 2 below.

[0102] Table 1

[0103]

[0104]

[0105] Table 2

[0106]

[0107] From the above results, it can be seen that compared with the absence of oxygen separation and the absence of SiO x Comparative Example 1, the silicon-based composite material obtained in Examples 1 to 6 contains SiO x , the silicon nanoparticles are bound and separated, the composite material has a higher structural strength, and the compacted specific surface area is only 2 to 10 times the original specific surface area, while the compacted specific surface area of ​​comparative example 1 increases to 116m 2 / g, which is 34.1 times the original specific surface area, and its compacted density is also relatively low. Further, the SiO xDue to the presence of, its volume expansion is significantly suppressed, the cycle stability is improved, and the capacity retention rate after 100 cycles is above 96%. Example 2 Since the pore volume of the porous carbon matrix is ​​small and the siliconization time is short, the silicon content of the obtained silicon-based composite material is low, so it has a lower gram capacity, but its cycle stability is excellent, and the capacity retention rate after 100 cycles reaches 99.2%. Example 3 Since the pore volume of the porous carbon matrix is ​​large and the siliconization time is correspondingly extended, the silicon content of the obtained silicon-based composite material is high, so it has a higher gram capacity and can also maintain good cycle stability, and the capacity retention rate after 100 cycles reaches 96.5%. The 100-cycle capacity retention rate of Comparative Example 1 is only 85.6%.

[0108] From the above analysis, it can be seen that the silicon-based composite material provided in the present application is achieved by loading a plurality of silicon particles with silicon nanoparticles as the core and an oxygen-rich layer as the shell on a porous substrate, and the oxygen content in the oxygen-rich layer varies in a gradient. This is not only beneficial to improving the conductivity of the silicon-based composite material, but also can utilize the oxygen-rich layer with a gradient variation in oxygen content to alleviate the volume expansion of silicon during the lithium insertion process, reduce the electrode expansion rate, improve the cycle stability of the battery, and extend the battery life.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A silicon-based composite material, characterized in that: The silicon-based composite material comprises silicon-based composite material particles, the silicon-based composite material particles comprise a porous substrate and silicon particles loaded in the pores of the porous substrate, the silicon particles comprise at least one silicon nanoparticle and an oxygen-rich layer at least partially coated on the silicon nanoparticle, and the material of the oxygen-rich layer is SiO x , 0<x≤2, and the oxygen content in the oxygen-rich layer changes gradiently along the direction from the center to the surface of the silicon nanoparticle.

2. The silicon-based composite material according to claim 1, characterized in that: The material of the silicon nanoparticles is elemental silicon, and the particle size of the silicon nanoparticles is 0.5 to 10 nm, preferably 0.5 to 2 nm; And / or, the thickness of the oxygen-rich layer is 0.5-5 nm, preferably 0.5-1 nm, and the thickness of the oxygen-rich layer is not greater than the particle size of the silicon nanoparticles.

3. The silicon-based composite material according to claim 1 or 2, characterized in that: The oxygen content in the oxygen-rich layer increases gradiently along a direction from the center to the surface of the silicon nanoparticle covered by the oxygen-rich layer.

4. The silicon-based composite material according to any one of claims 1 to 3, characterized in that: In the silicon-based composite material, the silicon content is 5 to 95 wt%, preferably 30 to 70 wt%; And / or, in the silicon-based composite material, the oxygen content is 0.5 to 10 wt%, preferably 1 to 5 wt%.

5. The silicon-based composite material according to any one of claims 1 to 4, characterized in that: The porous substrate comprises at least one of porous carbon, porous metal, porous metal oxide, porous metal-organic framework material, and porous organic-inorganic hybrid material; preferably, the specific surface area of ​​the porous substrate is 200 to 3000 m 2 / g, total pore volume is 0.2~3.0cm 3 / g; More preferably, the specific surface area of ​​the porous substrate is 600 to 2000 m 2 / g, total pore volume is 0.4~1.5cm 3 / g.

6. The silicon-based composite material according to any one of claims 1 to 5, characterized in that: The silicon-based composite material further comprises a coating layer, and the coating layer is coated on the surface of the silicon-based composite material particles; Preferably, the material of the coating layer includes one or more of a solid electrolyte, a conductive polymer, a carbonaceous material, a metal, an alloy, a metal oxide, a metal hydroxide, a metal halide, a metal sulfide, a metal phosphate, a boric acid compound, a sulfuric acid compound, a nitric acid compound, a polymetallic oxyacid salt, etc.; further preferably, the coating layer comprises a carbonaceous material; And / or, preferably, the coating layer has a thickness of 2 to 200 nm, preferably 2 to 50 nm, and more preferably 2 to 10 nm.

7. The silicon-based composite material according to any one of claims 1 to 6, characterized in that: The specific surface area of ​​the silicon-based composite material is 0.5 to 50 m 2 / g, preferably the specific surface area of ​​the silicon-based composite material is 0.5 to 10 m 2 / g; and / or, the compacted specific surface area of ​​the silicon-based composite material is 1 to 20 times, preferably 1 to 10 times, and more preferably 1 to 5 times, the specific surface area of ​​the silicon-based composite material; And / or, the compacted density of the silicon-based composite material is 0.8 to 1.5 g / cm 3 ; And / or, the resistivity of the silicon-based composite material is 1 to 1000 Ω·cm; And / or, the pH value of the silicon-based composite material is 3.0 to 7.5; And / or, the median particle size d of the silicon-based composite material V,50 5~20μm, diameter distance (d V,90 -d V,10 ) / d V,50 is 0.8 to 2.0; preferably, the median particle size d of the silicon-based composite material V,50 6~12μm, diameter distance (d V,90 -d V,10 ) / d V,50 It is 0.8~1.

2.

8. A method for preparing a silicon-based composite material, characterized in that: The preparation method comprises the following steps: Step S1, providing a porous substrate; Step S2, contacting the porous substrate with a silicon-containing precursor and an oxygen-containing precursor to perform silicon deposition and oxygen deposition to obtain the silicon-based composite material; Optionally, the preparation method further comprises step S3, which is arranged after step S2, of deep oxidation treatment; Optionally, the preparation method further includes a step S4, which is arranged after the step S2, for coating treatment.

9. The preparation method according to claim 8, characterized in that: The silicon-containing precursor includes at least one of monosilane, disilane, trisilane, halogenated silane, polysilane, silole and its derivatives, silanol and its derivatives; and / or, the oxygen-containing precursor comprises at least one of oxygen, carbon dioxide, water vapor, methanol, ethanol, n-propanol, isopropanol, butanol, acetone, and butanone; And / or, the temperature of the silicon deposition and the oxygen deposition are independently 200-1000° C., and the time is 0.5-100 h; And / or, the silicon-containing precursor and the oxygen-containing precursor are contacted with the porous matrix in a manner including: the silicon-containing precursor and the oxygen-containing precursor are contacted with the porous matrix alternately; or, the silicon-containing precursor and the oxygen-containing precursor are contacted with the porous matrix simultaneously; or, the silicon-containing precursor and a mixed gas containing the silicon-containing precursor and the oxygen-containing precursor are contacted with the porous matrix alternately, preferably, the silicon-containing precursor is continuously contacted with the porous matrix, and the oxygen-containing precursor is intermittently introduced during this process; And / or, the deep oxidation treatment includes chemical oxidation, solid-liquid separation and sintering performed in sequence, and the chemical oxidation includes: placing the composite material obtained after the silicon deposition and the oxygen treatment in a solution containing an oxidant for oxidation treatment; wherein the oxidant includes at least one of HNO3, H2SO4, acetic acid, propionic acid, butanol, butyric acid, succinic acid, malic acid, citric acid, and potassium permanganate.

10. A negative electrode, characterized in that: The negative electrode comprises a negative electrode active material, and the negative electrode active material is the silicon-based composite material according to any one of claims 1 to 7 or the silicon-based composite material obtained by the preparation method according to claim 8 or 9.

Citation Information

Cited By

  • Silicon-titanium composite material and preparation method and application thereof

    CN122338045A

  • Silicon-titanium composite material, preparation method and application thereof

    CN122338045B